Kedekatan Orang Tua Dengan Perkembangan Remaja Usia 13 – 14 Tahun - Alvrian Bertin Gebo; Saeri Tri Kusumo; Diyah Paramita (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: The growth and development of adolescents will vary from one adolescent to other teens who depends on a few things that influence it. Despite the potential for growth and development depend on the nature and pattern of growth, but is also influenced by the environment, in particular the influence of attention and affection that helps improve kesehatan.di Hamlet gig and Singosaren based on preliminary studies conducted there are many mothers who work and many teens are in let it do its own activities without the supervision of a parent.Objective: of this study was to determine the relationship between the proximity of the parents to the development of adolescents aged 13-14 years in the village of Bantul Imogiri WukirsariMethod. This type of research is a descriptive analytical study. Researchers create a picture or deskriptiftentang a situation objectively and how or why the phenomenon occurs. The total population is 40 people or populations are all mothers of children aged 13-14 years. Sampling techniques, namely the total sampling. Development and proximity data collected using a questionnaire.Results of the study in the village Wukirsari, Imogiri, Bantul, the data obtained from 40 respondents, the majority of respondents are mothers with parental closeness medium category, ie there are 17 respondents (42.5%), and most respondents are teenagers with enough adolescent development category , ie there are 16 respondents (40.0%).Conclusion. Kendall Tau test results indicate that, Kendall Tau correlation coefficient of 0.603 with a probability of 0.004. Because the probability value 0.000 <0.05 makadapat concluded that there are close relationship with the parents of adolescent development in the village Wukirsari, Imogiri, Bantul.Keyword: parental proximity, adolescent development